SAE Technical Paper Series 2007
DOI: 10.4271/2007-01-2712
|View full text |Cite
|
Sign up to set email alerts
|

Spray Development, Flow Interactions and Wall Impingement in a Direct-Injection Spark-Ignition Engine

Abstract: Levels of liquid fuel impingement on in-cylinder surfaces in direct injection spark ignition engines have typically been higher than those in port-fuel injection engines due to in-cylinder injection and higher injection pressures. The result is typically an increase in the levels of un-burned hydrocarbons and smoke emissions which reduce the potential fuel economy benefits associated with direct injection engines. Although different injection strategies can be used to reduce these effects to some extent, full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 15 publications
3
32
0
Order By: Relevance
“…one at the intake side and the other at the exhaust side of the engine. More details about the injector geometry, nozzle-hole angles and spray formation in a quiescent environment and in a running DISI engine can be found in previous studies by the current authors [3,4,[8][9][10].…”
Section: Injectormentioning
confidence: 99%
See 1 more Smart Citation
“…one at the intake side and the other at the exhaust side of the engine. More details about the injector geometry, nozzle-hole angles and spray formation in a quiescent environment and in a running DISI engine can be found in previous studies by the current authors [3,4,[8][9][10].…”
Section: Injectormentioning
confidence: 99%
“…towards the spark plug or any other in-cylinder area of interest, and by flexibility of when and how fuel is injected into the cylinder i.e. independence over piston position [2][3][4].…”
Section: Injection Systems For Direct-injection Spark-ignition Enginesmentioning
confidence: 99%
“…The investigation used the same injection system and facilities described in previous publications by the authors [22][23][24][25][26][27]. Therefore primarily deviations from standard equipment, i.e.…”
Section: Experimental Apparatus and Proceduresmentioning
confidence: 99%
“…This was achieved using a real-size optical nozzle to simulate the flow in one of 8 the holes of a real multi-hole injector previously used by the authors for macroscopic spray imaging and related engine studies [22][23][24][25][26][27]. These studies showed that the geometry and break-up of sprays from such injectors is significantly affected by operating conditions, which result in a high degree of superheating of the fuel components, i.e.…”
Section: Present Contributionmentioning
confidence: 99%
See 1 more Smart Citation